Study of the mechanism of pyrolysis and gasification of Mallee biomass - Yang, Yanwu (Curtin University, 2012)
Mechanisms of pyrolysis/gasification (steam and carbon dioxide) of mallee biomass were investigated. Wood biochar obtained under slow pyrolysis kept botanical structure but lost its original skeleton under fast pyrolysis. Both types of biochar can be used as CO2 sequestrater and soil amendment or be gasified to produce activated carbon (AC). Some inherent oxygen in biochar was transformed during steam gasification. Comparatively, CO2 gasification led to AC with lower specific reactivity, surface area, and micropore fraction.